The role of cultural heterogeneity in strengthening the link between family relationships and life satisfaction in 50 societies - Li, L. M. W. (2024)
We argue that the importance of family relationships for individual well-being varies across societies as a function of a society’s degree of cultural heterogeneity. To examine the role of family relationships, we analyzed the responses from 13,009 participants in 50 societies on their life satisfaction across societies varying in their levels of historical and contemporary cultural heterogeneity. Such heterogeneity creates differences in the frequency of interacting with unfamiliar groups, which leads families to become more central to their members’ satisfaction with life. Multi-level analyses showed that historical and contemporary cultural heterogeneity moderated the pattern such that greater historical or contemporary cultural heterogeneity of society promoted a stronger positive relation between family relationship satisfaction and individual life satisfaction. Our results also revealed that the moderating role of historical cultural heterogeneity was more reliable than that of contemporary cultural heterogeneity. These findings demonstrate the importance of societal demography in shaping people’s psychological processes in different historical periods, suggesting a universal, trans-historical cultural process.